Correlation of Social Support and Mother's Self-Management of Care for a Child with A Chronic Condition - Rinik Eko Kapti; Nurona Azizah; Aprilia Nur Kasanah; Luh Putu Tania Ambara Wati; Lilik Supriati; Ari Damayanti Wahyuningrum (Universitas STRADA Indonesia, 2025)
Background: Mothers caring for children with chronic conditions often experience physical and psychological exhaustion, which affects their ability to master the required self-management skills. Social support is needed by mothers to master self-management of childcare with chronic conditions. Purpose: To analyze the relationship between social support and maternal self-management Methods: This study used a quantitative descriptive method with a cross-sectional research design. Data collection used the Patient-Perceived Self-Management Tasks questionnaire and the MOS Social Support Survey Instrument by RAND. Both questionnaires had been tested for validity and reliability before being used. The population were mothers who care for children with chronic conditions. A total of 204 participants were included in this study. The sample was obtained using purposive sampling by approaching eligible mothers in pediatric inpatient wards at selected hospitals. Data analysis used the spearman correlation test. Results: This study shows that the greatest social support is from a partner, with an average of 83.25, and the lowest support is support from friends, with an average score of 61.24, while the average value of maternal self-management is 61.48. The results also show a relationship between social support, namely partner support, friend support and health worker support on self-management of mothers caring for children with chronic conditions, while there is no significant relationship between health worker support and self-management of mothers caring for children with chronic conditions. Conclusion: Health workers need to maximize the social support mothers receive so that mothers can master and practice adequate self-management to achieve optimal health for children with chronic conditions.